2019
DOI: 10.3390/cells8080920
|View full text |Cite
|
Sign up to set email alerts
|

The Snapdragon LATE ELONGATED HYPOCOTYL Plays A Dual Role in Activating Floral Growth and Scent Emission

Abstract: The plant circadian clock controls a large number of internal processes, including growth and metabolism. Scent emission displays a circadian pattern in many species such as the snapdragon. Here we show that knocking down LATE ELONGATED HYPOCOTYL in Antirrhinum majus affects growth and scent emission. In order to gain an understanding of the growth kinetics, we took a phenomic approach using in-house artificial vision systems, obtaining time-lapse videos. Wild type flowers showed a higher growth speed than kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ stress response 16 , the expression of seed storage proteins 17 , biomass production [18][19][20] , flower orientation 19 and flower scent emission [21][22][23][24] .…”
mentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ stress response 16 , the expression of seed storage proteins 17 , biomass production [18][19][20] , flower orientation 19 and flower scent emission [21][22][23][24] .…”
mentioning
confidence: 99%
“…The plant clock is an important coordinator of primary and secondary metabolism in plants. It defines the timing of floral scent emission and floral blend in a variety of plants including Antirrhinum majus, Nicotiana attenuatta , or Petunia [35,36,37,38]. The plant circadian clock appears to have a specific transcriptional structure in different tissues such as leaves, pods, seeds, or roots [13,14,75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Most flowers analyzed emit scent preferentially during the day or during the night. The LHY and ZTL orthologs control scent emission in Petunia , Nicotiana attenuata , and Antirrhinum majus [35,36,37,38]. The Solanaceae Petunia and Nicotiana emit higher quantities during the night, indicating an identity and circadian component controlling this trait [34,39].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves of Antirrhinum majus and A. linkianum revealed a gated growth pattern when analyzed with GAM fittings (Figure 3). Previous work has shown that flower growth in Antirrhinum majus has an asymptotic pattern and growth rate is controlled by the MYB circadian clock LATE ELONGATED HYPOCOTYL (AmLHY) [34]. The floral growth rate is not gated, indicating an organ-specific coordination of growth by the plant clock.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using the LUCIFERASE reporter genes in Arabidopsis and image acquisition paved the way to identify mutations in highly complex processes, such as circadian clock [32] or abiotic stress responses [33]. Further studies have used tobacco [14], petunia [10], tomato [21] or snapdragon [34] to identify diel growth patterns or the effect of gene knockdowns on growth. Both field and confined image-based phenomics share a common set of tools and solutions to acquire and process images.…”
Section: Introductionmentioning
confidence: 99%